2023
DOI: 10.1590/0103-8478cr20220256
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Aeromonas hydrophila isolates to antimicrobials and sanitizers

Abstract: In recent decades, Aeromonas hydrophila has emerged as a foodborne bacterial pathogen of public health concern, especially as it exhibits resistance to the major chemical sanitizers commonly used in the food industry. Meanwhile, this pathogen may be spread from diseased fish flesh through the contamination of equipment contact surfaces during food processing, thus posing a food safety risk. Thise determined the susceptibility profiles of retail fish-borne A. hydrophila isolates to 24 common antibiotics and fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…Fish resistance to AXE, TE, and NA was also higher (76% each). Chloramphenicol and gentamicin were the most effective antibiotics against A. hydrophila, which is consistent with the findings of Dhanapala et al (2021) and Kerigano et al (2023), who reported a 100% susceptibility to C. However, Martins et al (2023) found that although A. hydrophila were significantly resistant to AM (>89%), they were highly susceptible to TE (89.5%), CIP (78.9%), C and NA (68.4%), and AXE (47.4%). In addition, A. hydrophila has better resistance to C (60%) (Hafez et al, 2018) but was sensitive to SXT (56%) (Ahmed et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
“…Fish resistance to AXE, TE, and NA was also higher (76% each). Chloramphenicol and gentamicin were the most effective antibiotics against A. hydrophila, which is consistent with the findings of Dhanapala et al (2021) and Kerigano et al (2023), who reported a 100% susceptibility to C. However, Martins et al (2023) found that although A. hydrophila were significantly resistant to AM (>89%), they were highly susceptible to TE (89.5%), CIP (78.9%), C and NA (68.4%), and AXE (47.4%). In addition, A. hydrophila has better resistance to C (60%) (Hafez et al, 2018) but was sensitive to SXT (56%) (Ahmed et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
“…In humans, Aeromonas can cause gastrointestinal tract disorders and wound and soft tissue infections, as well as septicemia [44]. The multidrug-resistance of Aeromonas species is evidence of an emerging health problem in both humans and aquatic animals [45,46]. Aeromonas infections (including A. hydrophila infections) were the most widespread bacterial diseases occurring throughout the year in carps such as Catla catla, Labeo rohita, Cirrhinus mrigala, and Hypophthalmichthys molitrix [29].…”
Section: Bacteriamentioning
confidence: 99%